Implementasi Pembelajaran Berdiferensiasi Pada Mata Pelajaran Ilmu Pengetahuan Alam Dan Sosial (IPAS) Kelas V Sekolah Dasar: Penelitian - Brillianti. M; Hairida. H; Pranata. R; Kresnadi. H; Firmansyah.A (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The aim of this study was to provide a detailed account of the process and challenges involved in implementing differentiated learning in the areas of Natural and Social Sciences (IPAS) for fifth-grade students at SDN 03 Setalik. This study employs a qualitative research methodology, specifically utilising a descriptive approach. Data were gathered by interviews, observations, and documentation. The participants in this study were elementary school instructors in the fifth grade. The data validity examination employed the method of triangulation, utilising a combination of approaches and sources. The data was analysed using the Miles and Huberman technique, which consists of four stages: data collection, data reduction, data presentation, and drawing conclusions. Prior to developing a learning plan, the instructor assessed the learning requirements of the students by conducting a diagnostic assessment. Subsequently, a teaching module was created based on the findings of the diagnostic assessment. According to the evaluation results, grade V pupils exhibited visual, auditory, and kinaesthetic learning modalities. The teacher implemented differentiated instruction by tailoring the content, procedure, and product of the learning experience. The challenges encountered during this learning process were time-consuming, and the available facilities and learning resources were insufficient.